20,000 leagues under the sea [videorecording (DVD)] - Disney, Walt, 1901-1966; Fleischer, Richard; Verne, Jules, 1828-1905 (Disney DVD., 2003)
A trouble-shooting 19th century seaman is trying to discover why so many whaling ships have been disappearing of late. Teaming with a scientist and a diver, they set sail to investigate. They are promptly captured by the megalomaniac Captain Nemo, who skippers a lavish, scientifically advanced submarine.